(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Critical thinking skills greatly determine the quality of education, especially in biology students. This research aimed to determine the influence of Contextual Teaching and Learning (CTL) learning models based on gender on students’ critical thinking skills on human digestive system materials. This research uses quantitative research with experimental quasi research methods. The research design uses pretest-posttestnonequivalent control group design. The instrument used is a problem of essay tests that aim to find out the ability to think critically. Data analysis uses descriptive statistical analysis and inferential statistics. The results of the data analysis showed that there was a significant influence on the use of CTL learning models on critical thinking skills. The average value of pretest and posttest critical thinking skills in the experimental class was 40.71% and the control class was 29.14%. Gender has no significant effect on critical thinking skills in the material of the human digestive system. This is evidenced by the results of hypothesis tests that show that sig values. (2-tailed) > α was 0.677 > 0.05. The interaction of learning and gender models has no significant effect on critical thinking skills on the material of the human digestive system. This is evidenced by the results of hypothesis tests that show that sig values. (2-tailed) > α is 0.394 > 0.05. Thus, the results of this research provide recommendations so that teachers can apply the CTL learning model to students who have different gender characteristics in biological learning